A General Mathematical Method for Investigating the Thymic Microenvironment, Thymocyte Development, and Immunopathogenesis - Guanyu Wang; Gerhard R. F. Krueger (Mathematical Biosciences and Engineering)
T-lymphocyte (T-cell) development constitutes one of the basic andmost vital processes in immunology. The process is profoundlyaffected by the thymic microenvironment, the dysregulation of whichmay be the pathogenesis or the etiology of some diseases. On thebasis of a general conceptual framework, we have designed the firstbiophysical model to describe thymocyte development. Themicroclimate within the thymus, which is shaped by variouscytokines, is first conceptualized into a growth field$λ$ and a differentiation field$μ$, under the influence of which the thymocytesmature. A partial differential equation is then derived through theanalysis of an infinitesimal element of the flow of thymocytes. Ageneral method is presented to estimate the two fields based onexperimental data obtained by flow cytometric analysis of thethymus. Numerical examples are given for both normal and pathologicconditions. Our results are quite good, and even the time varyingfields can be accurately estimated. Our method has demonstrated itsgreat potential for the study of immunopathogenesis. The plan forimplementation of the method is addressed.